A Ten-Year Trend of Cutaneous Leishmaniasis at University of Gondar Hospital, Northwest Ethiopia: 2009-2018. (10th March 2021) - Zeleke, Ayalew Jejaw; Derso, Adane; Yeshanew, Arega; Mohammed, Rezika; Fikre, Helina
Abstract : Background . Cutaneous leishmaniasis (CL), which is one form of leishmaniasis, may show variations over years across regions, and epidemiological studies are crucial to estimate the cases of the disease status over a long time. This study is aimed at determining the trend of CL among patients at the University of Gondar Leishmaniasis Research and Treatment Center, northwest Ethiopia between 2009 and 2018 years. Methods . A ten-year data were extracted retrospectively. We included all patients who were visiting the center for CL diagnosis during the last ten years. Giemsa-stained skin slit microscopy was used to diagnose the disease. A chi-square test was used to compare the proportions of patients infected across years, seasons, months, sex, and age groups. Result . During the 10 years, a total of 1079 samples were requested for the diagnosis of CL. The cumulative average annual prevalence was found to be 55.4% (598/1079). The highest and lowest proportions of CL cases were recorded in 2014 (69.5%) and 2018 (35.4%), respectively. However, the percentage of CL cases did not show any significant differences over the study period. The number of suspected patients was significantly increased over the years (being lowest in 2009 and highest in 2017). The proportion of CL cases showed a remarkable difference across months but not seasons. CL was the highest within 15-49 years of age and males. Conclusion . The prevalence of CL did not show any significant differences over the last ten years. However, a remarkable increase of CL suspected cases was observed across the years. The disease showed significant association with age, sex, and months, but not seasons.